THE ROLE OF RAW MATERIALS FOR GEOPOLITICAL COMPETITION - PIOTR PUDŁO; WOJCIECH SKUZA (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article aims to present the most important issues of competition for raw materials, where different ideas of international trade are identified with political and financial pressure. The method of research used in the work is the analysis of literary heritage and historical facts that confirm or deny different theories. In particular, the theories of T. Malthus, neo-Malthusians and their opponents, as well as the struggle for oil and gas resources in the Middle East, the Arctic and the struggle for water resources in Central Asia were analyzed. In recent years, raw materials have become an instrument of international security. It is the struggle for sources of raw materials that is one of the decisive factors in world stability. Trade in resources should be the focus of regular observations to ensure geopolitical stability. In the modern world, much attention is paid to the problems and course of economic wars. What was unthinkable a decade ago is the norm today. Having a large army is mainly used to intimidate an opponent who is competing with a given country. Recent history provides numerous facts not only of political confrontation, but also of raging conflicts in the work for raw materials. States cannot remain indifferent to geopolitical relations over raw material resources. Dependence on the supply of raw materials from a single supplier allows to block efforts to diversify supplies, which may weaken its dominant position. Dominant suppliers of raw materials may exert political pressure on the recipient country. Financial problems of raw materials market participants are becoming an instrument of geopolitical competition. Internal crises are weakening the economies of suppliers and recipients of raw materials, making it easier to take control of their economies. Therefore, international control over trade in raw materials can become a factor of geopolitical stability.